D. H. Lawrence and “a shimmering protplasm” of art (Philologia, 2021)
The title of this paper is created after the words Paul Morel from Lawrence’s ﬁrst celebrated novel Sons and Lovers uses to interpret his still juvenile paintings, the words being prophetic of the still young author’s genuine drive to make his art a living thing. For David Herbert Lawrence art exists trembling between the immanent and the transcendent truth. For him, like for his many contemporaries, the greatness of art rests in the inconclusiveness of its form that, in the dialogical process inherent to it, always transcends the immediate present. Therefore, Lawrence argues, creation of a work of art, as well as the experience of art in general, if it be true, is always a “thought adventure”. In other words, to be true in a work of art means to consciously deny the inherited patterns of expression so that the ﬁnal text may testify of its own attempt to reach the other side of language and penetrate into the unspoken spheres of reality.
Keywords: form; transcendence; reality; experience; inconclusiveness; immediate present; thought adventure; other